Implementation of Digital-Based Al-Quran Reading and Writing Training Methods for Children in Pangkalan Village, Losarang District, Indramayu Regency - Carsinih; Tita Rizqiyah (Aslama: Journal of Islamic Studies, 2024)
The Qur'an is the word of Allah revealed to the Prophet Muhammad SAW. through the intermediary of the Angel Gabriel. As the people of the Prophet Muhammad SAW, we should practice and understand the importance of learning to read and write the Qur'an from an early age. One of the benefits of learning to read and write the Qur'an itself is that it can be a guide for those who read and practice it. Learning the Qur'an is not only in the Mosque or Prayer Room, etc. However, learning the Qur'an can be done only with gadgets, here the function of digitalization applies, especially in this sophisticated era. The method of implementing this socialization is by means of counseling and interactive face-to-face methods at TPQ Darul Istiqomah. The results of this socialization activity show that "Implementation of the Digital-Based Al-Qur'an Reading and Writing Training Method for Children in Pangkalan Village" provides motivation to children in Pangkalan Village, especially TPQ Darul Istiqomah, about the importance of learning to read and write the Qur'an from an early age. Then teach children about the use of gadgets in the digital era to learn to read and write the Qur'an using the Offline Translation of the Qur'an application. The obstacle in implementing this supporting program activity lies in the lack of training in reading and writing the Qur'an so that many children who memorize the Qur'an are weak in writing the verses of the Qur'an. Therefore, we try to overcome the existing problems and obstacles by carrying out a supporting program related to digital-based training in reading and writing the Qur'an for children in Pangkalan Village using the Offline Translation of the Qur'an application. The results of this article are that children are able to understand the importance of learning to read and write the Qur'an in everyday life and the level of enthusiasm of children at the Darul Istiqomah TPQ, Pangkalan Village is very good. and provide motivation to children in Pangkalan Village, especially TPQ Darul Istiqomah, about the importance of learning to read and write the Qur'an from an early age. Then teach children about the use of gadgets in the digital era to learn to read and write the Qur'an using the Offline Translation of the Qur'an application.